Correction Methods for Steady Incompressible Flows (Journal of Computational Mathematics, 1999)
Correction methods for the steady semi-periodic motion of incompressible fluid are investigated. The idea is similar to the influence matrix to solve the lack of vorticity boundary conditions. For any given boundary condition of the vorticity, the coupled vorticity-stream function formulation is solved. Then solve the governing equations with the correction boundary conditions to improve the solution. These equations are numerically solved by Fourier series truncation and finite difference method. The two numerical techniques are employed to treat the non-linear terms. The first method for small Reynolds number $R=0-50$ has the same results as that in M. Anwar and S.C.R. Dennis' report. The second one for $R>50$ obtains the reliable results.